Uncovering Themes in the Recent Literature on Performance Management in South African Local Government - Mohangi, Prashina; Nyika, Farai (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
Performance management has been practiced in the South African local government sector since the dawn of democracy in 1994. Municipalities have the autonomy to design and implement a performance management system (PMS) that is aligned with the municipal context. The current challenge in South African local government is that there is a lack of information on the effectiveness of performance management implementation at local government. The aim of this article was to provide a synthesis of the latest findings in the performance management literature in South Africa by highlighting themes. The methodology used is qualitative and relies on reviewing literature in the Google Scholar database between 2018 and 2023. This study finds that municipalities struggle with multiple challenges but there is a positive shift occurring in performance management related to a culture of compliance, the building of institutions and the relationship between the political and administrative arms of government.